2019
DOI: 10.1039/c9ra06305f
|View full text |Cite
|
Sign up to set email alerts
|

Microstructural free volume and dynamics of cryoprotective DMSO–water mixtures at low DMSO concentration

Abstract: Positron annihilation lifetime spectroscopy reveals changes in the DMSO–water microstructure in low concentrations of DMSO (1.8%, 2.0% and 10% v/v) that have a great impact on the cryoprotective effect during the cryopreservation of cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 53 publications
2
10
0
Order By: Relevance
“…In the past, it was shown that in a two-component water–DMSO mixture (without lipid bilayer), slow heating during the thawing led to a decrease of the o -Ps lifetime in the critical temperature range of 165 K to 200 K, as long as quick heating suppressed the drop-down of o -Ps lifetime, what was interpreted as avoiding the crystallization. 18 There is a work, 53 where a positive correlation was found between the cell post-thaw viability and the heating rate through the temperature range of 180 K to 200 K during thawing, what matches critical temperature range for crystallization of water–DMSO eutectic mixture observed in our experiments. It is known that during slow (equilibrium) cooling, biological cells are directly surrounded by the freeze-concentrated phase of cryoprotective agents and other dissolved substances in cryopreservation cell medium (inorganic salts, etc.…”
Section: Resultssupporting
confidence: 83%
See 4 more Smart Citations
“…In the past, it was shown that in a two-component water–DMSO mixture (without lipid bilayer), slow heating during the thawing led to a decrease of the o -Ps lifetime in the critical temperature range of 165 K to 200 K, as long as quick heating suppressed the drop-down of o -Ps lifetime, what was interpreted as avoiding the crystallization. 18 There is a work, 53 where a positive correlation was found between the cell post-thaw viability and the heating rate through the temperature range of 180 K to 200 K during thawing, what matches critical temperature range for crystallization of water–DMSO eutectic mixture observed in our experiments. It is known that during slow (equilibrium) cooling, biological cells are directly surrounded by the freeze-concentrated phase of cryoprotective agents and other dissolved substances in cryopreservation cell medium (inorganic salts, etc.…”
Section: Resultssupporting
confidence: 83%
“…[15][16][17] DMSO can form an amorphous fraction in the freezing mixture with water, which allows intracellular vitrication. 18,19 It was shown that this amorphous fraction consisting of freeze-concentrated DMSO is metastable and can crystallize during slow thawing, threatening cell viability. 18 In this work, the solidication and melting processes of water-DMSO mixtures containing liposomes were studied.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations